Polyphenols extracted from the Green Tea (Camellia sinensis) augments the protective immune responses in mice challanged with Salmonella typhimurium (Faculty of Medicine Universitas Indonesia, 2004)
Green tea is an aqueous infusion of dried unfermented leaves of Camellia sinensis. Numerous biological activities of green tea have been reported. The aqueous infusion and its polyphenolic substance are known for their activity as an antimutagenic, antibacterial, hypocholesterolemic, antioxidant, and mutagenic of B lymphocyte. Studies have demonstrated that green tea polyphenols increase IL-12 production. Salmonella spp infection is an important public health problem in many countries. Cell-mediated immunity (CMI), especially T-cell help is important for protection against this infection. Recent evidence indicates that IL-12 is one such factor that plays a crucial role in the development of CMI. These studies were carired out to investigate the effect of green tea polyphenols to the immune cellulare in mice responses of mice during Salmonella typhimurium infection. The subject consisted of 36 female mice (Balb/C), 6-8 weeks old, divided into 3 groups. The first group was given 10 mg polyphenols/mouse, the second group was given 5 mg polyphenols/mouse, and the third group as the control. In day 31, all mice were infected with 108 CFU Salmonella typhimurium orally. On day 0, 3, 5, and 7 postinfection, 3 mice from each groups were sacrificed, the splenocytes were extracted and cultured to measure the level of IFN-γ in the supernatan and. The peritoneal macrophages were also extracted and cultured to measure the phagocytic activity. The level of IFN-γ in splenocyte culture supernatant increased during infection in all groups, but the level of the experimental groups were higher than in control group. The percentage of phagocytic activity of peritoneal macrophages were higher in the experimental groups than in the control group. The increase of the phagocytic activities were seen corelate with the level of IFN-γ supernatan splenocyte culture. (Med J Indones 2004; 13: 1-7) Keywords: polyphenols, green tea, macrophages, phagocytosis